Faktor-faktor yang Memengaruhi Niat Beli Ulang Sayuran Melalui Platform E-Commerce di Jabodetabek - Pitaloka, Atika Dian; Hartoyo; Ali, Mochammad Mukti (Jurnal Aplikasi Bisnis dan Manajemen, 2022)
This study analyzes the factors that influence the buying intention of vegetables through e-commerce platforms in Jabodetabek through the variables of perceived ease of use, perceived usefulness, trust, attitude and satisfaction, formulates managerial implications and marketing strategies to increase consumer repurchase intention. This study involved 153 respondents who were selected by convenience sampling technique. Data were collected through questionnaires distributed online. The analysis used Structural Equation Modeling (SEM) with LISREL. The results showed that perceived ease of use had a significant effect on perceived usefulness, perceived usefulness and trust had a significant effect on attitude, attitude has a significant effect on satisfaction and satisfaction has a significant effect on repurchase intention. Managerial implications that can be carried out by vegetable entrepreneurs in e-commerce to increase repurchase intention are continuing to carry out strategies that can increase consumer trust and satisfaction. Keywords: repurchase intention, satisfaction, technology acceptance model, theory of reasoned action, vegetable e-commerce